Physiological mechanisms of intestinal absorbtion - S. T. Metelsky (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of the lecture. To discuss physiological mechanisms of absorbtion in gastro-intestinal tract (GIT).Original positions. In the literature data issues are covered from three sides: 1) topography of absorbtion of substances in various GIT segments: the stomach, duodenum, jejunum, ileum and the large intestine; 2) the basic functions of enterocytes; 3) the basic mechanisms of absorbtion in intestine. Seven basic mechanisms of absorbtion of substances in intestine are discussed.Conclusion. Of all GIT parts jejunum and ileum are characterized by the widest spectrum of absorbtion of various compounds. Comprehension of physiological mechanisms of absorbtion in small intestine is of great importance in practical gastroenterology.